Compound Specific Extraction of Camptothecin from Nothapodytes nimmoniana and Piperine from Piper nigrum Using Accelerated Solvent Extractor. (2nd January 2014) - Upadhya, Vinayak; Pai, Sandeep R.; Sharma, Ajay K.; Hegde, Harsha V.; Kholkute, Sanjiva D.; Joshi, Rajesh K.
Abstract : Effects of varying temperatures with constant pressure of solvent on extraction efficiency of two chemically different alkaloids were studied. Camptothecin (CPT) from stem of Nothapodytes nimmoniana (Grah.) Mabb. and piperine from the fruits of Piper nigrum L. were extracted using Accelerated Solvent Extractor (ASE). Three cycles of extraction for a particular sample cell at a given temperature assured complete extraction. CPT and piperine were determined and quantified by using a simple and efficient UFLC-PDA (245 and 343 nm) method. Temperature increased efficiency of extraction to yield higher amount of CPT, whereas temperature had diminutive effect on yield of piperine. Maximum yield for CPT was achieved at 80 ∘ C and for piperine at 40 ∘ C . Thus, the study determines compound specific extraction of CPT from N. nimmoniana and piperine from P. nigrum using ASE method. The present study indicates the use of this method for simple, fast, and accurate extraction of the compound of interest.